Abnormal Development of Glutamatergic Synapses Afferent to Dopaminergic Neurons of the Pink1−/− Mouse Model of Parkinson’s Disease - Pearlstein, Edouard; Michel, François J.; Save, Laurène; Ferrari, Diana C.; Hammond, Constance (Frontiers in Cellular Neuroscience, 2016)
In a preceding study, we showed that in adult pink1−/− mice, a monogenic animal model of Parkinson’s disease (PD), striatal neurons display aberrant electrical activities that precede the onset of overt clinical manifestations. Here, we tested the hypothesis that the maturation of dopaminergic (DA) neurons of the pink1−/− substantia nigra compacta (SNc) follows, from early stages on, a different developmental trajectory from age-matched wild type (wt) SNc DA neurons. We used immature (postnatal days P2–P10) and young adult (P30–P90) midbrain slices of pink1−/− mice expressing the green fluorescent protein in tyrosine hydroxylase (TH)-positive neurons. We report that the developmental sequence of N-Methyl-D-aspartic acid (NMDA) spontaneous excitatory postsynaptic currents (sEPSCs) is altered in pink1−/− SNc DA neurons, starting from shortly after birth. They lack the transient episode of high NMDA receptor-mediated neuronal activity characteristic of the immature stage of wt SNc DA neurons. The maturation of the membrane resistance of pink1−/− SNc DA neurons is also altered. Collectively, these observations suggest that electrical manifestations occurring shortly after birth in SNc DA neurons might lead to dysfunction in dopamine release and constitute an early pathogenic mechanism of PD.